2016
DOI: 10.1080/14737140.2016.1197122
|View full text |Cite
|
Sign up to set email alerts
|

Biology and management of clear cell sarcoma: state of the art and future perspectives

Abstract: In this review, we systematically discuss the current scientific evidence for the systemic treatment of CCS, including tyrosine kinase inhibitors, immunotherapy and MET inhibitors. Expert commentary: Recent insights in the biology of CCS have identified new potential therapeutic targets, which should be tested in prospective clinical trials. Whenever possible, patients with metastatic CCS should be included in clinical trials with good biological rationale. Innovative trial methodology and new regulatory mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 52 publications
0
46
0
3
Order By: Relevance
“…A phase I trial of an autologous GM-CSF-secreting tumor cell vaccine in advanced CCS patients demonstrated induction of T cell-mediated delayed-type hypersensitivity reactions to irradiated, autologous tumor cells [2]. Anecdotal reports in CCS patients have included a complete response to perilesional interferon-alpha, stable disease for 6–24 months in 2 patients following ipilimumab, and a partial response to pembrolizumab in a 6-year old [5]. Single modality radiotherapy would likely have limited efficacy in bulky, unresectable CCS [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A phase I trial of an autologous GM-CSF-secreting tumor cell vaccine in advanced CCS patients demonstrated induction of T cell-mediated delayed-type hypersensitivity reactions to irradiated, autologous tumor cells [2]. Anecdotal reports in CCS patients have included a complete response to perilesional interferon-alpha, stable disease for 6–24 months in 2 patients following ipilimumab, and a partial response to pembrolizumab in a 6-year old [5]. Single modality radiotherapy would likely have limited efficacy in bulky, unresectable CCS [16].…”
Section: Discussionmentioning
confidence: 99%
“…CCS shares striking histological and immunohistochemical similarities with cutaneous melanoma, often containing melanin pigment and expressing melanocyte differentiation antigens including S-100, HMB-45, and Melan-A [5]. Like melanoma and in contrast to most sarcomas, CCS is thought to derive from neural crest, spreads to regional lymph nodes in up to 50% of patients, and is frequently associated with in transit metastases [1, 2, 5]. CCS carries a high risk of hematogeneous dissemination with 5-year overall survival of 50–60% for localized disease and poor response to chemotherapy [1, 5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clear cell sarcoma (CCS) is a rare type comprising approximately 1% of all soft tissue sarcomas [1]. It was first described by Enzinger in 1965 [2], and for many years in the literature it was referred as to clear cell sarcoma of tendons and aponeuroses or malignant melanoma of soft tissue.…”
Section: Epidemiologymentioning
confidence: 99%
“…The grading of CCS, like other soft tissue sarcoma (STS), is based on the Fédération Française des Centres de Lutte Contre le Cancer (FNCLCC) system, which takes into account the degree of cell differentiation, necrosis, and mitotic activity. The CCS is characterized by a low mitotic index and a rare occurrence of necrosis, which is why most cases are classified as 1 or 2 malignancy [1,15].…”
Section: Biology Genetics and Histopathologymentioning
confidence: 99%